2009
DOI: 10.1080/10408360903044068
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: Regulation and role in disease

Abstract: Autophagy, a lysosomal process involved in the maintenance of cellular homeostasis, is responsible for the turnover of long-lived proteins and organelles that are either damaged or functionally redundant. The process is tightly controlled by the insulin-amino acid-mammalian target of the rapamycin-dependent signal-transduction pathway. Research in the last decade has indicated not only that autophagy provides cells with oxidizable substrate when nutrients become scarce but also that it can provide protection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
178
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(185 citation statements)
references
References 398 publications
(523 reference statements)
5
178
0
2
Order By: Relevance
“…Several recent reviews have been dedicated to the regulation of autophagy by signaling pathways [46,97,98]. In this section we would like to focus on signaling pathways with identified targets in the molecular machinery of autophagosome formation.…”
Section: Cytoplasmic and Nuclear Regulation Of Mammalian Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reviews have been dedicated to the regulation of autophagy by signaling pathways [46,97,98]. In this section we would like to focus on signaling pathways with identified targets in the molecular machinery of autophagosome formation.…”
Section: Cytoplasmic and Nuclear Regulation Of Mammalian Autophagymentioning
confidence: 99%
“…Signaling segments acting upstream of mTORC1 and mTORC2 that regulate autophagy have been discussed in recent reviews that the reader can consult for more information [46,98]. mTORC1 substrates and the regulation of autophagy As discussed above, ULK1, Atg13 and FIP200 form a stable complex that signals to the autophagic machinery downstream of mTORC1.…”
Section: Cytoplasmic Regulation Mtorc1 and Mtorc2mentioning
confidence: 99%
“…Autophagy is closely involved in the etiology of many important human diseases, including cancer, neurodegenerative diseases and metabolic disorders (Meijer and Codogno 2009).…”
Section: Autophagymentioning
confidence: 99%
“…Increasing studies have shown that autophagy is involved in many human diseases (such as neurodegenerative diseases and cancer) and plays roles in their pathogenesis [2,3] . Uncovering the role of autophagy in these diseases is essential because it may present a novel therapeutic target.…”
Section: Introductionmentioning
confidence: 99%